История христианской православной церкви - Смирнов П. (Типо-литогр. М.П. Фроловой, 1912)
Экземпляры: РК (19990223) / Инвентарный номер: 1031448 / Цена: 13.00 / Сис.шифр: 86.3 / Авт.знак: С 50 / ГРНТИ: 21 / ББК: 86.372